History and Efficiency of Perovskite Solar Cell (PSC) Source of Renewable Green Power: Advancements and Challenges in Perovskite Solar Cell Technology (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Perovskite is a calcium titanate mineral species. It has the properties of calcium titanium oxide.When originally tested in 2009, solar cells made from perovskites generated only around 3.5 of solarenergy into usable power. Efficiencies in hybrid perovskite solar cells have recently surpassed 20,prompting speculation that they would soon replace more conventional silicon photovoltaics. Recently,PSC topologies have been reduced from meso-structured to planar heterojunction, making it easier toachieve the goal of a low-cost, high-efficiency design in real-world applications. When exposed to air,oxygen and water vapor cause perovskites to destabilize over time. It's no secret that all nations arepaying closer attention to the advancement of renewable energy in light of the worldwide energy andenvironmental crises. Solar electricity, because to its cheap cost and abundant supply, is one of themost promising renewable energy sources. Despite significant advancements in high-performance solarcells over the last several decades, the high cost of modules remains a major barrier to widespread useof photovoltaic technology.